Characteristics of Firms Undertaking Seasoned Equity Offerings in China - ZHOU, YING (2012)
This paper employs the stock market and accounting data from the Chinese listed firms during 2004 to 2008 to identify and examine the effects of firm characteristics on the seasoned equity offering (SEO) decisions. Firms with higher market-to-book ratio, more growth opportunity, higher leverage, higher profitability, smaller size and longer period from the previous equity issue are more likely to conduct SEOs. The market timing, growth opportunity and trade-off theories can be used to explain the relationship between these characteristics and SEO issuance. The transition nature of economy and administrative intervention needs to be considered in the interpretation of the effects of the firm characteristics on the probability of SEO activities.